The Need for Applied Humanities in Postsecondary Technical/Vocational Education - Thiessen, Elmer J. (Canadian Journal of Higher Education, 1985)
In the fall of 1981, the Calgary Institute for the Humanities at the University of Calgary undertook a study of the need for the humanities in one and two-year technical/vocational programs in the ten public colleges and two technical institutes in the Province of Alberta. This study was commissioned by the Department of Advanced Education and Manpower. The research culminated in a report entitled, "The Humanities in Alberta Postsecondary Technical and Vocational Education." The object of this paper is to review the major findings and recommendations of this Report. A central thrust of the report in terms of improving the humanities component in technical/vocational programs has to do with the need to teach the humanities in such a way as to relate to the needs and interests of students in these programs. Various implications that evolve from this central emphasis on the needfor applied humanities are reviewed in this paper.